Challenges and Opportunities in Public Hospital Administration in India - Bansal, Mamta; Rawat, Nitin; Nain, Arvind; Bhupinder, Bhupinder; Vanshika, Vanshika; Rana, Praveen Singh; Kartic, Kartic (Journal of Neonatal Surgery, 2025)
For a large percentage of India's low-income population, public hospitals serve as their main source of healthcare, providing necessary medical care despite socioeconomic inequalities. However, a number of systemic issues impede these institutions' capacity to provide quality healthcare. Inadequate infrastructure, a significant lack of healthcare professionals, pervasive corruption, and shortcomings in policy execution are some of the most urgent problems. These barriers restrict access for individuals in need while also lowering the standard of care. However, there are also encouraging prospects for change in the industry. Opportunities to enhance the healthcare system are provided by legislative changes like the Ayushman Bharat movement, the expanding trend for medical tourism, and technological developments. In order to gain a greater insight into how strategic investments, public-private partnerships (PPPs), and technological advancements might close the current gaps in infrastructure, workforce, and healthcare delivery, this article aims to investigate these dynamics through the analysis of secondary data. The study's main hypothesis is that systemic reforms will enhance the accessibility, caliber, and impartiality of healthcare services provided by India's public hospitals while taking advantage of these opportunities. The study intends to draw attention to India's potential for a public healthcare system that is more efficient, just, and long-lasting